HUBUNGAN METODE PEMBELAJARAN BRAINSTORMING TIPE ROUND ROBIN TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI PEMBELAJARAN TEMATIK KELAS V SDN 9 KAYUAGUNG - Nahaya Fatricia; Rury Rizhaldi; Bambang Hermansah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This study aims to determine whether or not there is a relationship between the Round Robin type of Brainstorming Learning Method and Student Learning Motivation in Class V Thematic Learning Materials at SDN 9 Kayuagung. The research method used in this study is a quantitative research method with a correlation type. Data collection techniques used by researchers in this study were interviews, questionnaires and documentation. The results of this study indicate that from the results of the product correlation test the moment of the relationship between the Round Robin Type Brainstorming Learning Method on Student Motivation in Class V Thematic Learning at SD Negeri 9 Kayuagung. Which has a value of (r count) while the r-table value is 0.404, and 0.700 > 0.404 or r-count > r-table. Thus it can be concluded that Ho is rejected and Ha is accepted or in other words there is a positive relationship between variable X (brainstorming type round robin learning method) and variable Y (student learning motivation). The level of relationship between variables X and Y lies in the interval 0.60-0.799, which means that the relationship between the two is strong. This shows that there is a significant positive relationship between the round robin type brainstorming learning method on student motivation in the thematic learning materials for class V SDN 9 Kayuagung.